Prevalence of Extended-Spectrum Beta-Lactamase-Producing Enterobacteriaceae Causing Bloodstream Infections in Cancer Patients from Southwest of Iran - Abbasi Montazeri, Effat (Infect Drug Resist, 2020)
INTRODUCTION: This study aimed to evaluate the frequency rate of extended-spectrum beta-lactamase-producing Enterobacteriaceae (ESBL-PE) causing bloodstream infections (BSIs) in cancer patients referred to one of the major referral hospitals in Ahvaz city, southwest Iran. MATERIALS AND METHODS: In this study, 1700 blood cultures were collected from 610 cancer patients suspected to have BSI from October 2016 to August 2017 referred to the Shafa cancer hospital, Ahvaz, southwest of Iran. The blood culture bottles were incubated aerobically at 35–37ºC for 24 hours and then sub-cultured on routine microbiology culture media. The bacterial colonies were identified using standard tests. The antibiotic susceptibility testing was achieved by the disc-diffusion method. The phenotypic detection of ESBLs was carried out by the combination disc-diffusion test (CDDT). Finally, the polymerase chain reaction (PCR) was performed to investigate the presence of bla(TEM), bla(CTX), bla(SHV,) and bla(PER) genes. RESULTS: The prevalence of BSI in cancer patients was 16.4% (100/610). Gram-negative rods with rate of 74% (74/100) were the most prevalent bacteria. The frequency of Enterobacteriaceae family was 21% including Escherichia coli (n: 8), Klebsiella pneumoniae (n: 6), Enterobacter spp. (n: 5), Citrobacter freundii (n: 1), and Serratia marcescens (n: 1). All isolates were multidrug-resistant (resistance to three or more antibiotics). The results of CDDT showed that 42.8% (9/21) of Enterobacteriaceae isolates had a positive ESBL test of which 100% (9/9) indicated positive band for at least one of the ESBL genes by PCR method. The bla(CTX-M) and bla(TEM) genes were detected in 38% (8/21) and 23.8% (5/21) of isolates, respectively, while the bla(SHV) and bla(PER) were not detected in any isolates. CONCLUSION: Based on the results, surveillance, and antibiotic stewardship programs should be implemented for cancer patients to prevent the spread of more ESBL-PE that have limited therapeutically choices.